The effects of customer relationship management (CRM) on e-commerce evolution: A systematic review - Nogueira, Edithe Oliveira; Borchardt, Miriam (Technium Social Sciences Journal, 2022)
The developments triggered by marketing technologies in the information system of companies that took place in the mid-1990s through the tools of knowledge management, data mining, data quality, and social CRM, became effective in the construction of new business environments. The system called Customer Relationship Management (CRM), which has been widely disseminated in the business environment, has been one of the factors that makes relationship marketing in company management manage all relationships with customers. CRM is more than marketing, as it allows its management, sales and new business, and consequently impacts the evolution of e-commerce. Thus, the objective of this research is to identify and explore the effects of customer relationship management on the evolution of e-commerce and what its potential would be. We used a methodology with a qualitative approach, descriptive and exploratory, by systematic mapping method and deductive hypothetical, whose data collection technique was the systematic literature review research, seeking international articles in the databases indexed in the Capes platform (scopus), in the period 2015/2018, related to the theme. Inclusion and exclusion criteria through selection of articles performed by software: VosViewer and Excel. Electronic commerce is becoming more and more prevalent because it is characterized by easy access to information, being an ubiquitous trade with low transaction costs, which in an abstract place contributes to the realization of an economic market.